Clinical And Morphological Features of Liver Damage in Patients with Insulin Resistance - Mari N. Ella, Yeva M. Oliver, James Z. Chloe (Academic Journal of Clinicians, 2025)
The increasing prevalence of MS, and, as a consequence, the increase in the number of diseases that are complications of this pathology determines the relevance of the MS problem. At present, the etiologic factors of MS have not been fully studied, but the leading role of carbohydrate metabolism disorders is highlighted. Many organs and systems of the human body participate in carbohydrate metabolism, and great importance is attached to those factors that reflect damage to glycolysis processes. Therefore, special attention is paid to the liver as the main organ participating in the process of gluconeogenesis. In the process of mechanisms of damage to carbohydrate metabolism, the liver acts not only as an organ in which metabolic disorders are formed, but is also a target organ itself. One of the main manifestations of pathological changes in carbohydrate metabolism, in which the liver also participates, is obesity. The common pathogenesis, close associations with other manifestations of insulin resistance (IR) allow us to consider non-alcoholic fatty liver disease (NAFLD) as liver damage in MS. The concept of non-alcoholic NAFLD is clearly defined and covers a spectrum of liver lesions, including fatty degeneration (FD), fatty degeneration with inflammation and damage to hepatocytes - non-alcoholic (metabolic) steatohepatitis (NASH) and fibrosis (with the possibility of progression to cirrhosis). The prevalence of NAFLD in the general population is 14-25%